Community modelling: a technique for enhancing local capacity to engage with flood risk management - Landstrom, C; Becker, M; Odoni, N; Whatmore, S (Elsevier, 2018)
Widening acceptance of the value of public participation in local flood risk management (FRM) brings new challenges. A key issue is the capacity of local communities to participate in expert-led FRM. Community Modelling (CM) is a technique developed to enhance local ability to engage with water management. Drawing on participatory research in geography and science studies the technique has four core elements: resource minimalism, strategic participant recruitment, standardised software and actively making connections with decision makers. We introduce CM and illustrate it with a case study of local FRM in England. In the example case free computer software, known amongst technical experts, was used to coproduce representations of local flooding problem with a small group affected residents. Guided by a natural science modeller the group examined the causes of local flooding and considered possible mitigation measures. Social science expertise facilitated interaction with local flood risk managers, technical experts and decision making authorities.